2015
DOI: 10.1161/jaha.115.002308
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Mortality Outcomes in the Elderly With Impaired Cardiac and Pulmonary Function: The Cardiovascular Health Study (CHS)

Abstract: BackgroundImpaired pulmonary function (IPF) and left ventricular systolic dysfunction (LVSD) are prevalent in the elderly and are associated with significant morbidity and mortality. The main objectives of this study were to examine the relative impact and joint association of IPF and LVSD with heart failure, cardiovascular mortality and all‐cause mortality, and their impact on risk classification using a continuous net reclassification index.Methods and ResultsWe followed 2342 adults without prevalent cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In general and middle-aged populations, studies found an association of FEV 1 with mortality 19 21 , and partly showed that FEV 1 was a better predictor than FVC 22 , while other studies reported a stronger association with FVC and less (or no) association with FEV 1 or airway obstruction 1 3 . In older populations, an association with FEV 1 23 and airway obstruction with all‐cause mortality 24 has been reported. We observed also a clear association for FEV 1 /FVC.…”
Section: Discussionmentioning
confidence: 97%
“…In general and middle-aged populations, studies found an association of FEV 1 with mortality 19 21 , and partly showed that FEV 1 was a better predictor than FVC 22 , while other studies reported a stronger association with FVC and less (or no) association with FEV 1 or airway obstruction 1 3 . In older populations, an association with FEV 1 23 and airway obstruction with all‐cause mortality 24 has been reported. We observed also a clear association for FEV 1 /FVC.…”
Section: Discussionmentioning
confidence: 97%
“…Waheed et al . [ 20 ] have shown that impaired pulmonary function and cardiovascular functions are prevalent in the elderly and are an important cause of cardiovascular and all-cause mortality. They have recommended that isolated prevalence of either pulmonary or cardiovascular comorbidity can contribute to overall cardiovascular outcomes and have also recommended a comprehensive cardiac and pulmonary evaluation in the prediction of cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…4). Impaired pulmonary function has been linked to greater risks of ill health and all-cause mortality [81]. In addition to being a reliable measure of pulmonary function, PEF has been shown to be a valid measure of overall health status and all-cause mortality [82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%